2017
DOI: 10.1186/s13256-017-1482-1
|View full text |Cite
|
Sign up to set email alerts
|

Pneumomediastinum following a prolonged second stage of labor – an emphasis on early diagnosis and conservative management: a case report

Abstract: BackgroundEsophageal rupture is an extremely rare condition to occur to a pregnant or postnatal woman. Esophageal ruptures have been previously described in the literature; however, they are most common in the setting of hyperemesis gravidarum.Case presentationThis case report describes a 27-year-old white woman who began complaining of central chest pain and shortness of breath 3 hours after a normal vaginal delivery, with no history of vomiting antenatally or intrapartum. A chest X-ray and computed tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A Boerhaave's syndrome diagnosis is based on CT imaging that can demonstrate esophageal wall edema and periesophageal fluid, which in the present case excluded it. It should be noted that this syndrome can occur rarely in postpartum with just 200 cases reported globally [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Boerhaave's syndrome diagnosis is based on CT imaging that can demonstrate esophageal wall edema and periesophageal fluid, which in the present case excluded it. It should be noted that this syndrome can occur rarely in postpartum with just 200 cases reported globally [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors have reported pneumomediastinum that developed in pregnancy due to prolonged labour course. In each case, differentiating esophageal rupture from its more benign alternative of alveolar membrane rupture was undertaken 1–4. All of these cases were treated conservatively although Whelan et al ultimately concluded that esophageal rupture was present.…”
Section: Discussionmentioning
confidence: 99%
“…Hamman’s syndrome is characterised by spontaneous pneumomediastinum and subcutaneous emphysema, most frequently secondary to barotrauma from increased intrathoracic pressure. Persistently high intrathoracic pressure is seen in two pregnancy-associated conditions: hyperemesis gravidarum and prolonged second stage of labour 1. The incidence of pregnancy-related pneumomediastinum is only 1:100 000 2.…”
Section: Introductionmentioning
confidence: 99%